Clinical profile and comorbidities associated with rheumatoid arthritis patients in Sudair, Saudi Arabia - Fehaid Alanazi (Wolters Kluwer Medknow Publications, 2021)
Background: Rheumatoid arthritis (RA) is a chronic, debilitating condition that has a significant effect on the lives of patients, their families, and society at large. Aims: The aim is to determine the clinical profile and any comorbidities associated with RA patients in the Sudair region of Saudi Arabia. Subjects and Methods: Sixty patients were included in this cross-sectional observational study, both newly or already diagnosed with RA, fulfilling the 2010 American College of Rheumatology/European League Against Rheumatism Classification Criteria for RA. They were followed up in the rheumatology clinic in King Khalid Majmaah Hospital in the Majmaah province from January 2017 to December 2020. Results: The subjects' mean age was 47.87 ± 11.55 years, 52 female and 8 male (female-to-male ratio 6.5:1). About 23.3% of patients with RA had positive family history. The main comorbidities and associated diseases were hypertension (18.3%) and hypothyroidism (15%). The most frequently involved joints were the wrist, metacarpophalangeal, proximal interphalangeal, elbow, and knee joints. Subjects were positive in 66.7% for rheumatoid factor and 78.3% for anti-cyclic citrullinated peptide. Both markers were positive in 60% of the patients. Conclusion: Approximately one-quarter of the studied group had a family history of RA. Hypertension followed by hypothyroidism was the most common comorbidities reported in our study.